Variety of Jordan algebras in small dimensions - Kashuba, I. (Algebra and Discrete Mathematics, 2006)
The variety J orn of Jordan unitary algebra structures on k n , k an algebraically closed field with char k 6= 2 , is studied, as well as infinitesimal deformations of Jordan algebras. Also we establish the list of GLn-orbits on J orn, n = 4, 5 under the action of structural transport. The numbers jor₄ and jor₅ of irreducible components are 3 and 6 respectively; a list of generic structures is included.